Мегаполис как источник страхов в перспективе массовой литературы (антология „Мифы мегаполиса”) - Radosz, Joanna (Studia Rossica Posnaniensia, 2019)
The anthology Myths of Megapolis (Mify megapolisa), published in 2007, due to the variety of the presented short stories shows various perspectives of the metropolis’ life and the fears of its citizens. The article discusses and classifies these fears and analyses their connection with the substance of the metropolis itself.